1997
DOI: 10.1136/tc.6.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and smoking cessation among older adults: United States, 1965-94

Abstract: Given the projected increase in the elderly population, the medical and economic consequences of smoking will become a greater burden in the next decades. Therefore, focusing attention on cessation among the elderly is an immediate and urgent priority for public health professionals and clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
68
1
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 28 publications
10
68
1
7
Order By: Relevance
“…The prevalence of current smoking was three times greater among men than among women. The prevalence among aged males (31%) in Bambuí was much higher than that observed among men (≥65 years) in the United States (13%), 8 United Kingdom (18%) 4 and Canada (20%). 19 Among women, this prevalence (10%) was fairly similar to that observed in the United States (11%) 8 and slightly lower than the prevalence found in the United Kingdom (17%) 4 and Canada (14%).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The prevalence of current smoking was three times greater among men than among women. The prevalence among aged males (31%) in Bambuí was much higher than that observed among men (≥65 years) in the United States (13%), 8 United Kingdom (18%) 4 and Canada (20%). 19 Among women, this prevalence (10%) was fairly similar to that observed in the United States (11%) 8 and slightly lower than the prevalence found in the United Kingdom (17%) 4 and Canada (14%).…”
Section: Discussionmentioning
confidence: 88%
“…The prevalence among aged males (31%) in Bambuí was much higher than that observed among men (≥65 years) in the United States (13%), 8 United Kingdom (18%) 4 and Canada (20%). 19 Among women, this prevalence (10%) was fairly similar to that observed in the United States (11%) 8 and slightly lower than the prevalence found in the United Kingdom (17%) 4 and Canada (14%). 19 In addition to the higher prevalence of smoking among men in the present study, they started to smoke earlier and consumed a larger number of cigarettes per day, which is similar to that observed in the North American population.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…1 Despite increasing public awareness of the health risks inherent in the use of tobacco products and legislation that reduces the availability of cigarettes and prohibits smoking in many public facilities, virtually no further reduction in smoking prevalence has occurred in the US since 1990. 2 This phenomenon is largely attributable to nicotine dependence, a genetically complex disorder. [3][4][5][6] Many twin studies have revealed that there is a strong genetic component in nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%